If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -3) = 7x + 21 Reorder the terms: 3(-3 + 2x) = 7x + 21 (-3 * 3 + 2x * 3) = 7x + 21 (-9 + 6x) = 7x + 21 Reorder the terms: -9 + 6x = 21 + 7x Solving -9 + 6x = 21 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -9 + 6x + -7x = 21 + 7x + -7x Combine like terms: 6x + -7x = -1x -9 + -1x = 21 + 7x + -7x Combine like terms: 7x + -7x = 0 -9 + -1x = 21 + 0 -9 + -1x = 21 Add '9' to each side of the equation. -9 + 9 + -1x = 21 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 21 + 9 -1x = 21 + 9 Combine like terms: 21 + 9 = 30 -1x = 30 Divide each side by '-1'. x = -30 Simplifying x = -30
| Y=5x-0.5x | | 10000=x^2+x | | -6(10-4r)=-3(-12-8f) | | 10x+7-2x=x-2+8x | | 10x+7=x-2+8x | | 12-10(5x+4)+4x= | | 16*5*3.14= | | 3.14*16*5= | | 6b+4-2b=6b | | (2x+8)(3x+24)=0 | | 90+x+34+x+64=180 | | -6x^3+9x^2+6x= | | .5y-4=33.33y-3 | | y-3x=-5y | | 5x+10=5x-10 | | 23b+70=40b-100 | | 12a+95=26a-87 | | a+56=3a+46 | | 3mn^3/14x^2y/9n^4/7x^4y^3 | | 6-2x^2=0 | | 15u+80=71u-88 | | 22s-64=15s+13 | | 2w+82=32w-98 | | ax=7-bx | | 11b+30=30b-84 | | 31m-4=21m+76 | | -6x-42=-35 | | 42f-100=27f-25 | | h+76=2h+23 | | 2/4(x+8)=1/3(x+27) | | (6x-3)+2=5x | | 4k-4k-1=48 |